Preparation of intrinsic antibacterial silicone rubber with matrix tethering quaternary ammonium salt groups. (March 2021) - Dong, Fuying; Jia, Tiansong; Wang, Qin; Liu, Yang; Ma, Lixia; Li, Shuaijie; Tang, Xinde; Feng, Shengyu
Graphical abstract: Highlights: An intrinsic antibacterial silicone rubber was designed with the antibacterial agent grafted on the main chain of the matrix via covalent bond. The silicone rubber exhibits excellent antibacterial activity and antibacterial durability against both S. aureus and E. coli. The hydrophilicity of silicone rubber could be adjusted by the content of QAS groups. Abstract: The immobilization of the antibacterial agent in the matrix is crucial to endow materials with excellent antibacterial activity. In this paper, a strategy was presented to prevent the antibacterial agent leaching out from the cross-linking network of silicone rubber via construction of the matrix tethering quaternary ammonium salt (QAS) groups by covalent bond. A series of hydroxyl-terminated polysiloxanes with pendent QAS groups were prepared and characterized. The polysiloxanes were subsequently used as a matrix for preparing an intrinsic antibacterial silicone rubber. SEM analysis indicated a high compatibility of the formulations of silicone rubber. The silicone rubber exhibits excellent antibacterial activity against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Most importantly, the silicone rubber exhibits prominent durability of antibacterial activity even after staying in the natural environment for 3 months. Moreover, the hydrophilicity of silicone rubber could be adjusted by the content of QAS groups.